Digital Literacy and Positive Bystander Intervention in Preventing Adolescent Cyberbullying - Hamzah, Radja Erland; Putri, Citra Eka; Saifulloh, Muhammad; Pranawukir, Iswahyu (NAJAHA, 2025)
The rapid growth of internet technology and social media penetration in Indonesia increases the risk of cyberbullying among adolescents. Therefore, digital literacy-based interventions and positive bystander empowerment are needed to build a safe and empathetic digital culture. This study aims to design a digital literacy-based communication model for positive bystander interventions in preventing cyberbullying among adolescents in Jakarta, West Java, and North Sumatra, taking into account variations in digital exposure and sociocultural contexts. The research method used a naturalistic qualitative approach with a descriptive case study, collecting primary data through observation, in-depth interviews, and Focus Group Discussions (FGDs), as well as secondary data from documentation and literature. The FGD results indicate that digital literacy is key to shaping adolescents' proactive attitudes. In Medan, participants who had not previously received digital literacy training demonstrated high enthusiasm, awareness of social media, and courage to oppose cyberbullying in line with Batak cultural values. In Depok, participants acknowledged the importance of digital literacy, but limited parental and teacher supervision limited their involvement. In Jakarta, adolescents were more rationally mature, but apathy, urban behavior, and minimal community supervision limited the implementation of interventions. Overall, digital literacy improved adolescents' ability to assess information, understand ethical consequences, and act constructively in the face of cyberbullying. The research yielded an interactive communication model that positions adolescents as active participants, strengthens ethical skills and courage, and encourages engagement with peers, families, schools, and digital platforms to create a proactive cyberbullying prevention ecosystem. Future research is recommended to test the model's effectiveness on a larger scale and conduct longitudinal evaluations of online prosocial behavior.